LGG-09. PD-L1 EXPRESSION IN PEDIATRIC LOW GRADE GLIOMAS, AN OPPORTUNITY FOR INTERVENTION INDEPENDENT OF BRAF MUTATIONAL STATUS. (23rd April 2019) - Martin, Allison; Bell, Robert; Yuan, Ming; Harris, Lauren; Arnold, Antje; Poore, Brad; Asnaghi, Laura; Raabe, Eric; Eberhart, Charles
Abstract: 10–15% of all pediatric gliomas harbor a point mutation in the BRAF gene, BRAF V600E, and it is especially common in certain low grade subtypes. Targeting this mutation with BRAF inhibitors has generated impressive responses in pediatric brain tumor patients with multiple clinical trials ongoing. In melanoma, where BRAF V600E mutation is common, responses to BRAF inhibition have been robust but not durable. However, long term remission has been achieved with immune checkpoint inhibitors, including those of the programmed death (PD) pathway. Response to PD inhibition has been linked to the expression of PD-L1 on the surface of tumor cells. To evaluate a potential relationship between BRAF V600E mutation and PD-L1 expression, we examined the expression of PD-L1 in pediatric high and low grade glioma cell lines as well as a cohort of pediatric low grade glioma patient samples of diverse and rare histologic subtypes. Transient transfection of BRAF wild-type cell lines with a plasmid expressing mutant BRAF V600E increased baseline PD-L1 expression in 2 of 3 cell lines. Moreover, a BRAF V600E mutant cell line also had high baseline PD-L1 expression. All tumors in our cohort expressed PD-L1, and some cases had high levels, >50%. There was a trend toward increased PD-L1 in the BRAF mutant cases but some wild-type tumors also had robust expression. These findings suggest that the programmed death pathway may be active in subsets of pediatric low grade glioma as a mechanism of immune evasion regardless of BRAF mutational status. Although low grade gliomas often have excellent overall survival when they can be removed surgically, unresectable tumors are associated with significant morbidity and often present a treatment challenge for the neuro-oncologist. Clinical trials evaluating the effect of PD pathway inhibitors in pediatric low grade glioma patients will be critical in determining whether PD-L1 expression indicates a likely therapeutic benefit.